Assessment of welfare indicators in dairy farms offering pasture at differing levels. (28th March 2019) - Armbrecht, L.; Lambertz, C.; Albers, D.; Gauly, M.
Abstract : In terms of animal welfare, farming systems of dairy cows are perceived positively by consumers when compared to pigs or poultry. A main reason is that the majority of consumers associate dairy farming with pasture, which in turn they relate with benefits for animal health and welfare. However, holistic scientific assessments of the effects of pasturing on animal welfare are rare. Hence, it was the aim to study the animal welfare level in 61 German loose housing dairy farms by using the measures of the Welfare Quality ® protocol for dairy cattle (WQP). Data were collected twice per farm at the end of the pasture season (July to October) and approximately 6 months later at the end of the barn season (December to April). Farms were classified based on the duration cows had access to pasture per day during the pasture season: group 1 (G1)>10 h; group 2 (G2) 6 to 10 h; group 3 (G3)<6 h and group 4 (G4) without pasture access. The average herd size was 129 Holstein-Friesian or Red-Holstein cows (range 58 to 527). In addition to WQP data, performance data were gathered from routine herd data recordings. The indicators were aggregated to criteria applying the scoring system of the WQP. G4 received lower scores at the first than at the second visit for the criterion absence of hunger, while there were no differences between visits in the other groups ( P =0.58 – group×farm visit effect). All pasturing groups were scored better at the end of the pasture season than G4 for the criterion comfort around resting ( P <0.01). Compared with G1 for both farm visits and G2 for the end of the barn season, G4 reached inferior scores for the criterion absence of injuries, including indicators such as hairless patches, lesions, and swellings and lameness . At both assessments G2 was scored higher than the other groups for the criterion absence of diseases ( P =0.04). In conclusion, pasture access had positive effects only on selected welfare indicators, however, these effects were not maintained throughout the barn season.